Feasibility of septal body volume reduction for patients with nasal obstruction. (30th January 2015) - Yu, Myeong Sang; Kim, Jong‐Yeup; Kim, Bo‐Hyung; Kang, Sung‐Ho; Lim, Dae Jun
<x xml:space="preserve">Abstract</x> Objective Septal body hypertrophy, like inferior turbinate hypertrophy, can result in changes to the nasal cross‐sectional area and resistance to airflow. The aim of this study is to evaluate the efficacy of septal body volume reduction (SBVR) for the treatment of septal body hypertrophy in patients with nasal obstruction. Study Design Prospective randomized study. Methods The study was conducted on two groups (51 patients) with symptoms and signs of nasal obstruction associated with septal body and inferior turbinate hypertrophy that were refractory to medical therapy. In the turbinoplasty only (ITR) group (n = 25), conventional turbinoplasty was only performed on the inferior turbinate. In the septal body reduction (SBR) group (n = 26), concurrent bilateral microdebrider‐assisted SBVR was performed during the turbinate surgery. Results The nasal symptoms, including nasal obstruction, rhinorrhea, itching, and sneezing, had significantly improved at 3 months after treatment in both groups (P < 0.001). Improvement of nasal obstruction in the SBR group was greater than that in the ITR group at 3 months (P < 0.05). Acoustic rhinometry demonstrated a significant increase in the cross‐sectional area and nasal volume in both groups 3 months after surgery. The postoperative change in nasal volume was higher in the SBR group (P < 0.05). No adverse reactions such as bleeding, infection, adhesions, or olfactory changes were encountered in the SBR group. Conclusions Combined SBVR and turbinoplasty appears to be more effective than turbinoplasty alone for the treatment of nasal obstruction in patients with inferior turbinate and septal body hypertrophy. Level of Evidence 1b. Laryngoscope, 125:1523–1528, 2015